Adoption level of sustainable construction practices: A study on Malaysia’s construction stakeholders - Osman, Wan Nadzri; Mohamed Udin, Zulkifli; Salleh, Dani (IBIMA Publishing, 2012)
Purpose - For this research, the concept of sustainability had been divided into two different perspectives which include the financial sustainability performance (economics aspect) and non financial sustainability performance (environment and social aspect). Design/methodology/approach – A survey method was employed due to the reason that it is the most appropriate research design to obtain personal and social facts, beliefs, and attitude on a large scale. Since the data of analysis is done at the company level, the unit of analysis for this research is the construction stakeholder’s organization. Findings – The result of this study shows that the adoption level of financial sustainability is better than non financial sustainability. Originality / value – This paper attempts to identify the current level of sustainable construction performance among the Malaysian construction stakeholders.